2018
DOI: 10.1371/journal.pone.0193361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a first responder on survival outcomes after out-of-hospital cardiac arrest occurs during a period of exercise in a public place

Abstract: IntroductionThe deployment of first responders in a public place is one of the interventions that is used for increasing bystander cardiopulmonary resuscitation (CPR) of out-of-hospital cardiac arrests (OHCA). We studied the association between the presence of a first responder and the survival of OHCA that occurred during a period of exercise in a public place.MethodsAll of the adult OHCAs of a presumed cardiac etiology that occurred during a period of exercise in a public place and that were witnessed by a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Fourth, our study showed that frequent CPR training is a feature of most FR-systems, as would be expected. Previous research has highlighted the superiority of off-duty medical professionals over laypersons [30] and more recent studies have shown the positive impact of trained citizen-responders on neurological outcomes [31]. Some regions allow citizen-responders to register as FRs without validating CPR-training (e.g., Denmark: Capital region and Central region), whereas CPR training is mandatory in two other regions in Denmark (Region Zealand and Region Southern Denmark).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our study showed that frequent CPR training is a feature of most FR-systems, as would be expected. Previous research has highlighted the superiority of off-duty medical professionals over laypersons [30] and more recent studies have shown the positive impact of trained citizen-responders on neurological outcomes [31]. Some regions allow citizen-responders to register as FRs without validating CPR-training (e.g., Denmark: Capital region and Central region), whereas CPR training is mandatory in two other regions in Denmark (Region Zealand and Region Southern Denmark).…”
Section: Discussionmentioning
confidence: 99%
“…In our locality, this is mostly through private arrangements using any available vehicle from family, friends or commercial taxis. It is a sharp contrast to what obtains in the western world where emergency dispatchers, fi rst responders, Basic Life Support (BLS) or Advanced Cardiac Life Support (ACLS) ambulances are engaged [4,5]. 5(1): 007-012.…”
Section: Introductionmentioning
confidence: 96%
“…In other countries, either a medical background is required (e.g., Emergency Medical Services personnel, nurses, and doctors), or professionals with the duty of help are FRs (e.g., firemen, police officers, and security personnel) [4][5][6][7]. In some countries, FR systems combine these groups [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Early CPR and defibrillation have been shown to be effective to improve outcome after out-of-hospital cardiac arrests [6][7][8][9][10][11][12][13]. However, early CPR by trained CPR providers is critical, as the 1-month survival for patients suffering out-of-hospital cardiac arrests is higher if the rescuers are trained in CPR, compared to untrained bystanders [14].…”
Section: Introductionmentioning
confidence: 99%